Export competitiveness dynamics of indonesian black and white pepper in the ASEAN market: evidence from RCA and ECI analysis, 2014–2023 - Henny Rosmawati; Endang Lastinawati; Putri Ayu Ogari; Windi Lestari; Yetty Oktarina; Annisya Balqis Maharani (Journal of Agricultural Socio-Economics (JASE), 2026)
Indonesia is one of the world’s major pepper producers, and ASEAN remains an important export market for Indonesian black and white pepper. However, export performance has fluctuated over the last decade due to production instability, price volatility, competition from Vietnam, and changing market requirements. This study analyzes export dynamics and evaluates the comparative and dynamic competitive advantages of Indonesian black and white pepper in the ASEAN market during 2014–2023. The study contributes to the literature by separately examining black and white pepper in major ASEAN destination markets using Revealed Comparative Advantage (RCA) and Export Competitiveness Index (ECI) analyses. Secondary time-series data on export volume and value were obtained from UN Comtrade, ITC Trade Map, FAOSTAT, Statistics Indonesia, and the Ministry of Agriculture, using HS codes 090411 for black pepper and 090412 for white pepper. Results show that Indonesian pepper exports to ASEAN were highly volatile. Black pepper exports to Vietnam declined after peaking in 2015, while white pepper exports displayed unstable performance across destination markets. RCA results indicate strong comparative advantages for black pepper exports to Vietnam and Singapore and for white pepper exports to Malaysia. However, ECI findings reveal fluctuating dynamic competitiveness, particularly for white pepper exports. Strengthening Indonesia’s pepper export competitiveness requires improvements in post-harvest handling, standardization of quality standards, value-added processing, logistics efficiency, and compliance with export and sanitary standards. Stronger farmer–exporter linkages and value-chain upgrading are also needed to enhance the long-term competitiveness of Indonesia’s smallholder-based pepper agribusiness in the ASEAN market.